The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/cce.0000000000000450
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Approaches to Preparing Notes for Analysis With Natural Language Processing on the Performance of Prediction Models in Intensive Care

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The impact of preprocessing methods on the model performance can be significant and those methods are therefore essential to report. 30 The sparse Bag-of-Words and TFIDF representations and the dense word and document embeddings were most frequently used and we found an association between the types of text representation and machine learning methods. The neural network methods generally used a dense text representation, while regularized logistic regression methods, random forests, or SVMs largely took sparse representations as input.…”
Section: Discussionmentioning
confidence: 78%
“…The impact of preprocessing methods on the model performance can be significant and those methods are therefore essential to report. 30 The sparse Bag-of-Words and TFIDF representations and the dense word and document embeddings were most frequently used and we found an association between the types of text representation and machine learning methods. The neural network methods generally used a dense text representation, while regularized logistic regression methods, random forests, or SVMs largely took sparse representations as input.…”
Section: Discussionmentioning
confidence: 78%
“…Relevant for us is the fact that stemming has been shown to add semantic value in feature selection, as for example Biba and Gjati (2014) proved that stemming of composite words greatly improves classification of fake news. Moreover, Mahendra et al (2021) showed that cleaning and stemming resulted in the greatest model performance on the medical domain for the task in mortality prediction on ICU (Intensive Care Unit) patients. We refer readers to a thorough survey of stemmers spanning over the past 50 years by Singh and Gupta (2016).…”
Section: Related Workmentioning
confidence: 99%
“…To give just one example, the word vectors produced contain both the adjective and adverb forms of the word 12 . Mahendra et al 13 used the Term Frequency-Inverse Document Frequency technique to find a middle ground between the advantages of the association between words and documents and words and corpus. They overcame the problem of existing word vectors not being able to effectively present a document’s data.…”
Section: Research Reviewmentioning
confidence: 99%
“…They overcame the problem of existing word vectors not being able to effectively present a document’s data. It turned out that word2vec works well when combined with the estimated word weights 13 . Yadav et al 14 employed Convolutional Neural Networks (CNNs) in conjunction with attention mechanisms, leveraging deep learning techniques to develop a digital system for managing ICH and creating an automatic classification model.…”
Section: Research Reviewmentioning
confidence: 99%